Caspase Cleavage of Gelsolin Is an Inductive Cue for Pathologic Cardiac Hypertrophy - Putinski, Charis; Abdul‐Ghani, Mohammad; Brunette, Steve; Burgon, Patrick G.; Megeney, Lynn A. (Journal of the American Heart Association, 2018)
Background Cardiac hypertrophy is an adaptive remodeling event that may improve or diminish contractile performance of the heart. Physiologic and pathologic hypertrophy yield distinct outcomes, yet both are dependent on caspase-directed proteolysis. This suggests that each form of myocardial growth may derive from a specific caspase cleavage event(s). We examined whether caspase 3 cleavage of the actin capping/severing protein gelsolin is essential for the development of pathologic hypertrophy. Methods and Results Caspase targeting of gelsolin was established through protein analysis of hypertrophic cardiomyocytes and mass spectrometry mapping of cleavage sites. Pathologic agonists induced late-stage caspase-mediated cleavage of gelsolin. The requirement of caspase-mediated gelsolin cleavage for hypertrophy induction was evaluated in primary cardiomyocytes by cell size analysis, monitoring of prohypertrophy markers, and measurement of hypertrophy-related transcription activity. The in vivo impact of caspase-mediated cleavage was investigated by echo-guided intramyocardial injection of adenoviral-expressed gelsolin. Expression of the N-terminal gelsolin caspase cleavage fragment was necessary and sufficient to cause pathologic remodeling in isolated cardiomyocytes and the intact heart, whereas expression of a noncleavable form prevents cardiac remodeling. Alterations in myocardium structure and function were determined by echocardiography and end-stage cardiomyocyte cell size analysis. Gelsolin secretion was also monitored for its impact on naïve cells using competitive antibody trapping, demonstrating that hypertrophic agonist stimulation of cardiomyocytes leads to gelsolin secretion, which induces hypertrophy in naïve cells. Conclusions These results suggest that cell autonomous caspase cleavage of gelsolin is essential for pathologic hypertrophy and that cardiomyocyte secretion of gelsolin may accelerate this negative remodeling response.